Assessment of Burnout Levels Before and During COVID-19 Pandemic: A Web-Based Survey by the (Italian) Association of Medical Endocrinologists (AME) - Loscalzo, Yura; Marucci, Simonetta; Garofalo, Piernicola; Attanasio, Roberto; Lisco, Giuseppe; De Geronimo, Vincenzo; Guastamacchia, Edoardo; Giannini, Marco; Triggiani, Vincenzo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Some endocrinologists were involved in the management of patients with suspected or confirmed COVID-19 during the first wave of the pandemic. This study aims to analyze burnout levels among the Association of Medical Endocrinologists (AME) members before and during the pandemic. Methods: We recruited two AME members samples at two different times: before COVID-19 (n = 811) and during the first wave of the ongoing pandemic (n = 579). Both the samples filled the Maslach Burnout Inventory. We performed MANOVAs to evaluate demographic and COVID-19 related differences in burnout levels and Pearson’s Chi-square test to compare burnout severity before and during the pandemic. Results: Women reported higher Emotional Exhaustion and reduced Professional Accomplishment than men. The oldest physicians had lower levels of Emotional Exhaustion and Depersonalization and higher Professional Accomplishment than younger workers. Independent contractors displayed lower levels of burnout compared to established contractors. Finally, the pandemic, per se, did not lead to changes in burnout levels. Discussion: Women and young physicians are at higher risk of burnout. It is also possible that front- line professionals are at higher risk during a health care crisis. Moreover, it is likely that the length of exposure to the pandemic has not been sufficient to impact burnout levels. Conclusion: Short-term exposure to pandemic-related activities seemed to have a low impact on burnout severity, except for physicians directly involved in managing COVID-19 cases. It is strongly recommended the availability of psychological support in public hospitals.
Keywords: Burnout